Нормативне забезпечення шкільної фізкультурної освіти на національному рівні у країнах ЄС - Скальські, Даріуш (Studies in Comparative Education, 2015)
Cтаттю присвячено характеристиці національних стратегій фізкультурної освіти у країнах Європейського Союзу. Внаслідок проведеного аналізу зроблено висновок, що, хоча цілі національних стратегій відрізняються у різних країнах, існує спільне бачення напрямів упровадження змін у країнах ЄС. Згідно з ним, найбільш важливими чинниками покращення фізкультурної освіти в цих країнах вважають: інфраструктуру, шкільний і позашкільний спорт, здоровий спосіб життя, інклюзію, збільшення кількості уроків, збільшення кількості змагань, соціалізацію, професійний розвиток фахівців. Статья посвящена характеристике национальных стратегий физкультурного образования в странах Европейского Союза. На основе проведенного анализа сделан вывод, что цели национальных стратегий отличаются в разных странах, но у них есть общее видение направлений внедрения изменений в странах ЕС. Согласно ему, наиболее важными факторами улучшения физкультурного образования в этих странах считают инфраструктуру, школьный и внешкольный спорт, здоровый образ жизни, инклюзию, увеличение количества уроков, увеличение количества соревнований, социализацию, профессиональное развитие специалистов. The article is dedicated to the description of national strategies of physical education in EU countries. On the basis of analysis it has been concluded, that in some countries (i.e. Latvia and Lithuania) the strategies concentrate on the Primary and Secondary school within a broader strategy, and in other countries they focus on the youth (Great Britain). Some strategies are developed purely for the field of Physical Education and Sports (i.e. Bulgaria, Spain and Croatia) with a broad field of a target group coverage. In a number of strategies the necessity of paying particular attention to certain target groups (children and youth with special needs, girls, talented sportsmen etc.) is stressed. Aims of national strategies differ in different countries and this is defined by the complex of sociopolitical, socioeconomic and cultural and educational priorities. However, there is a common vision of ways of changes application in EU countries. According to this, the most important factors of physical education improvement in these countries are: infrastructure, school and out-of-school sports, healthy lifestyle, inclusion, increasing of lessons number, increasing of competitions number, socialization, and professional development of experts. It is concluded that national strategies aim at implementation or adaptation of measures, directed at increasing of awareness of social and educational importance of population’s physical and sports activity during life. The reforms, as results of national strategies implementation, are governed by priorities defined in them. These reforms can be directed at modernization of physical education curriculums, at maintaining of physical education teachers’ professional development, at financing of various regional and local initiatives.